An evaluation of the virtual simulated surgery assessment for the induction and return to practice scheme. Issue 5 (3rd September 2022) - Khan, Anwar; Burrows, Peter; Scallan, Samantha; Lyon-Maris, Johnny
ABSTRACT: This paper reports on the development of the virtual Simulated Surgery assessment for the Induction and Return to practice (I&R) scheme and how it was used in the assessment of clinical and consultation skills. The evaluation examines the reliability and consistency of the virtual Simulated Surgery with the face-to-face assessment and reports feedback from the participants (candidates, administrators, marshals, examiners and role-players), highlighting what is lost and/or gained by the difference in format. Finally, the paper discusses the benefits and problems of remote assessment generally and looks at how this mode of assessment may be used in the future.